Principios para la Formalización de la Ingeniería de Software - Bolanos Castro, Sandro Javier; Medina García, Victor Hugo; Joyanes Aguilar, Luis (Ingeniería, 2008)
In this article a proposal is presented for a software engineering based on the premise of establishing a necessary set of principles to formalize a body of knowledge guided not alone for work activities, methods and technical but also strengthened by properties that indeed can be used and applied without there is discrimination in the project type that it is carried out.